2013
DOI: 10.1371/journal.pone.0079026
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Sucrose Responsiveness in Apis mellifera and A. cerana Foragers

Abstract: In the European honey bee, Apis mellifera, pollen foragers have a higher sucrose responsiveness than nectar foragers when tested using a proboscis extension response (PER) assay. In addition, Africanized honey bees have a higher sucrose responsiveness than European honey bees. Based on the biology of the Eastern honey bee, A. cerana, we hypothesized that A. cerana should also have a higher responsiveness to sucrose than A. mellifera. To test this hypothesis, we compared the sucrose thresholds of pollen forager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
(15 reference statements)
3
14
0
Order By: Relevance
“…By contrast, the percentage of A. mellifera exhibiting PER ranged from 68% to 100%. Consistent with previous studies (Yang et al, 2013), our study revealed that A. mellifera was more responsive to sucrose than A. cerana. In the six consecutive acquisition trials, both honey bee species were unresponsive to CS in the first acquisition trial, indicating that there were no sensitization responses in the honey bees.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, the percentage of A. mellifera exhibiting PER ranged from 68% to 100%. Consistent with previous studies (Yang et al, 2013), our study revealed that A. mellifera was more responsive to sucrose than A. cerana. In the six consecutive acquisition trials, both honey bee species were unresponsive to CS in the first acquisition trial, indicating that there were no sensitization responses in the honey bees.…”
Section: Discussionsupporting
confidence: 93%
“…In some of these studies, behaviors in mixed species colonies and in their own colonies were compared. The behaviors of worker reproductive physiology (Tan et al 2009a), thermoregulation (Yang et al 2010c), defense against wasp (Tan et al 2012b), brood recognition ability (Tan et al 2009b), and proboscis extension response to sugar syrup (Yang et al 2013) in mixed species colonies were consistent with behaviors in their own colonies. These results suggest that mixed species colonies are useful tools to compare the differences between behaviors of different species of honey bees.…”
Section: Discussionmentioning
confidence: 59%
“…With more foraging trips, Ac will increase the amount of nectar brought into the colonies when all other conditions are equal. However, Am foragers carry heavier nectar loads than Ac (51.0 ± 1.9 vs 31.3 ± 1.2 mg) (Tan et al 2012a), while the two species of foragers show no different sugar concentrations in collected nectar (Yang et al 2013). The longer foraging life, more foragers and more foraging trips of Ac will increase the amount of nectar brought into colonies.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations